Unemployment and Opioid-Related Mortality Rates in U.S. Counties: Investigating Social Capital and Social Isolation-Smoking Pathways. (15th September 2021) - Yang, Tse-Chuan; Kim, Seulki; Matthews, Stephen A
Abstract: We examine two mechanisms–social capital and socio-behavior–potentially linking unemployment rates to opioid-related mortality and investigate whether the mechanisms differ geographically by the pace of the opioid crisis. Applying path analysis techniques to 2015–2017 opioid-related mortality in U.S. counties (N=2, 648), we find that (1) high unemployment rates are not directly associated with opioid-related mortality rates; (2) high unemployment rates are negatively associated with social capital, and low social capital contributes to high opioid-related mortality; (3) high unemployment rates increase social isolation and the prevalence of smoking, which is positively related to opioid-related mortality; and (4) the pathways are stronger among counties in the states experiencing a rapid growth in opioid-related mortality rates than among those states that are not. Our findings offer insight into how unemployment rates shape the opioid crisis and suggest that the relationship between unemployment and opioid-related mortality is complex.